LEGAL PROTECTION OF PERSONAL DATA BASED ON REGULATION IN INDONESIA - Jumriani Nawawi (Jurnal Al-Dustur, 2022)
This research focused on how positive law provides legal protection against the use of personal data in Indonesia. This research aims to find out the various problems related to legal protection of the use of personal data based on human rights principles by providing benefits and guarantees of legal certainty for the public against the protection of personal data both electronically and non-electronically. This type of research is normative juridical research. Research is carried out qualitatively by relying on library research studies. The results showed that forms of abuse such as theft and the sale of personal data violate the law in information technology and can also be categorized as a violation of human rights because personal data is part of human rights that must be protected. Legal protection of personal data in Indonesia from a positive legal perspective has been realized by several regulations that regulate. Still, no one has comprehensively regulated the protection of personal data.